A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil - Santos, Marcus Thadeu Teixeira; de Oliveira, Sílvia Helena; de Carvalho, Thiago Ribeiro; Zaidan, Bárbara Fernandes; Da Silva, Nelson Rodrigues; Berneck, Bianca Von Müller; Garcia, Paulo Christiano Anchietta (Zootaxa, 2019)
A new species of Paratelmatobius is described from the Brazilian Atlantic Forest in the state of Paraná in southern Brazil. Adults, tadpoles, and vocalizations are described. Morphological traits and phylogenetic analysis place the new species within the P. cardosoi group. The new species can be readily distinguished from its congeners by its advertisement call being composed of two note types and comprised of a series of 2–4 notes. The new species is classified as an explosive breeder, having reproductive activity strongly associated with heavy rainfall. This discovery highlights the importance of intensifying survey efforts in the Atlantic Forest, a domain with high levels of species richness and endemism.